2009
DOI: 10.1080/15622970802505800
|View full text |Cite
|
Sign up to set email alerts
|

Delusion of pregnancy associated with antipsychotic induced metabolic syndrome

Abstract: Metabolic syndrome is currently the research topic of several studies. Although physical manifestations of metabolic syndrome have been described, the psychological and psychiatric impact of metabolic syndrome has not been studied to date. We report the first case of antipsychotic-induced metabolic syndrome which was associated with development of delusions of pregnancy in a post-menopausal woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…[5] In the narration of the case, authors also described the sense of fetal movements and concluded that the patient had pseudocyesis. [5] If the association of pseudocyesis and rise in prolactin level is taken into consideration, manifestations of our case are similar to the description of delusion of pregnancy associated with antipsychotic-induced increased prolactin levels. [1234] However, cases in one of these series only had delusion of pregnancy without associated signs and symptoms of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In the narration of the case, authors also described the sense of fetal movements and concluded that the patient had pseudocyesis. [5] If the association of pseudocyesis and rise in prolactin level is taken into consideration, manifestations of our case are similar to the description of delusion of pregnancy associated with antipsychotic-induced increased prolactin levels. [1234] However, cases in one of these series only had delusion of pregnancy without associated signs and symptoms of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In this case report, we present a case of pseudocyesis with delusional belief of being pregnant developing in the background of increased prolactin levels and metabolic syndrome associated with use of antipsychotics and expand the limited literature on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic-induced metabolic syndrome also gives rise to features that may further fuel this delusion, such as widening abdominal girth and breast tenderness/engorgement [22]. The high estrogen levels in the early luteal phase of the menstrual cycle similarly result in such effects on the body.…”
Section: Possible Theories Behind the Delusions Of Pregnancymentioning
confidence: 99%
“…This overlapping phenotype is indicative of dysfunction of similar brain systems and pathways. 39 Frontal, temporal and hippocampal atrophy, 57 and regionally specific reductions in the anterior corpus callosum 58,59 and anterior hippocampus 60,61 have been described in MRI studies of both FTD and schizophrenia. There is not a shared convincing evidence in support of FTD rather than a psychosis involving the frontal lobe.…”
Section: Delusion Of Pregnancy and Dementiamentioning
confidence: 99%